Electrocatalytic oxidations and reductions in ionic liquids - Muhammad, Sayyar (2016)
In this thesis, surface electrocatalysis of several energy-conversion-relevant redox reactions in ionic liquid electrolytes is described. The first oxidation process investigated is the formation of surface oxide films on Pt electrodes by trace water oxidation in protic ionic liquids (PILs). This is followed by investigation of the oxidation of hydrazine (N2H4), formic acid (HCOOH), ethanol (EtOH) and dimethyl ether (DME) in PILs and a description of the role played by surface oxides during each oxidation process. Finally, the electrocatalytic reduction of CO2 at a variety of electrode materials is explored in room temperature aprotic ionic liquids. The data reveal that the surfaces of Pt electrodes become covered with oxide layers due to oxidation of trace water, which is omnipresent in PILs, at positive potentials (E > 1.0 V vs. Pd-H). X-ray photoelectron spectroscopy (XPS) shows that the oxide layers grow to form thick films as the potential is made more positive and as the temperature and water concentration of the PILs are increased. The mechanism and kinetics of oxide film growth are also discussed. Voltammetric analysis shows that the presence of residual surface oxides activates Pt electrodes towards electrooxidation of N2H4. Furthermore, immersion of oxidized Pt electrodes in N2H4-containing PILs deactivates the electrode indicating that N2H4 reacts with the residual surface oxides. Oxidation of HCOOH at Pt catalyst in PILs occurs mainly by dehydration plus COads oxidation at a potential that coincides with the onset of the formation of Pt surface oxides. Compared to Pt electrocatalysts, the overpotential for electrooxidation of HCOOH is higher at Au catalyst but lower at Pd catalyst. Oxidation of trace water in PILs at Pt also plays a pivotal role during the electrocatalytic oxidation of EtOH and DME in the PILs. Oxidation of both EtOH and DME coincides with coverage of the Pt surface by the adsorbed oxide species that helps to activate both processes by oxidizing the adsorbed poisoning CO and CO-like intermediate species via a 'bifunctional' reaction mechanism. Generally, higher overpotentials are observed for each oxidation, and higher activation energies are measured for EtOH oxidation in PILs than in aqueous electrolytes. Finally, it is shown that CO2 electroreduction takes place at lower overpotentials at Au and Ag electrocatalysts than at Cu, Pt and boron doped diamond (BDD) electrodes in the presence of ionic liquid electrolytes. Ag electrocatalysts reduce CO2 at ~0.2 V lower potential when 1-ethyl-3-methylimidazolium ethylsulphate [emim][EtSO4] is used as supporting electrolyte in acetonitrile compared to when the conventional supporting electrolyte tetrabutylammonium hexaflourophosphate [TBA][PF6] is used. CO is a product of CO2 reduction at Ag catalyst and the results highlight that Ag and imidazolium-based ILs could be a promising system for reduction of CO2 to CO at low overpotentials.